An Advanced Study on the Impact of Varying Degrees of Underground Accidental Explosions on Underground Pipes by Simulation - Olarewaju, Akinola Johnson (International Research in Environment, Geography and Earth Science Vol. 9, 2021)
Underground accidental explosions are caused by the detonation of solid, liquid or gas explosive materials stored below the ground surface. Underground explosion can take place, broadly speaking, in sand as well as undrained clay with varying degrees of impact on underground structures. In this study, effects on underground pipes due to varying degrees of underground accidental explosions were studied using ABAQUS numerical code. Pipes buried in loose sand, dense sand and undrained clay at various depths below the ground surface were modelled. The material properties as revealed by several researchers were used. Pipe and soil materials were limited to linear, elastic, homogeneous and isotropic. The observed parameters are displacement, pressure, mises, stress and strain at the crown, invert and spring-line of vertically and horizontally buried underground pipes. The results showed that irrespective of the ground media, displacement increases linearly as the loading wave velocity increases while clay soil (i. e. undrained clay) is problematic. Even though there is wide variation in the results due to dilations and compressions caused by the transient stress pulse of compression wave, observed parameters increases as the loading wave velocity increases. This study has demonstrated that higher loading wave velocity would result to higher displacement which invariably would result to higher induced moment and stress if multiplied by the corresponding distances. As a result of this, there is need for accidental explosion resistant evaluation of underground installations like pipes in order to have an optimal design of underground structures like pipes that would resist the effects of underground accidental explosions.